Circumferential Strain as a Marker of Vessel Reactivity in Patients with Intradialytic Hypotension - Maciej Goździk; Sergiusz Ustyniak; Anna Zawiasa-Bryszewska; Agnieszka Płuciennik; Maja Nowicka; Magdalena Kaczmarska; Ludomir Stefańczyk; Ilona Kurnatowska (Medicina, 2023)
Background and Objectives: Intradialytic hypotension (IDH) complicates 4 to 39.9% of hemodialysis (HD) sessions. Vessels’ reactivity disturbances may be responsible for this complication. Two-dimensional speckle tracking is used to assess arterial circumferential strain (CS) as a marker of the effectiveness of the cardiovascular response to the reduction of circulating plasma. Materials and Methods: The common carotid artery (CCA) and common iliac artery (CIA) CSs were recorded using ultrasonography in 68 chronically dialyzed patients before and after one HD session. Results: In patients with IDH episodes (n = 26), the CCA-CS was significantly lower both before (6.28 ± 2.34 vs. 4.63 ± 1.74 p = 0.003) and after HD (5.00 (3.53–6.78) vs. 3.79 ± 1.47 p = 0.010) than it was in patients without this complication. No relationship was observed between CIA-CS and IDH. IDH patients had a significantly higher UF rate; however, they did not differ compared to complication-free patients either in anthropometric or laboratory parameters. Conclusions: Patients with IDH were characterized by lower pre- and post-HD circumferential strain of the common carotid artery. The lower CCA-CS showed that impaired vascular reactivity is one of the most important risk factors for this complication’s occurrence.